Nutritional causes of anemia in Mexican children under 5 years: results from the 2006 National Health and Nutrition Survey Causas nutricionales de anemia en niños menores de 5 años: resultados de la Encuesta Nacional de Salud y Nutrición 2006 - Vanessa De la Cruz-Góngora; Salvador Villalpando; Rosario Rebollar; Teresa Shamah-Levy; Ignacio Méndez-Gómez Humarán (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To describe the frequency and severity of anemia and the nutritional variables associated to hemoglobin levels (Hb) in children <5 years of age. MATERIALS AND METHODS: We studied 981 children measuring hemoglobin and serum concentrations of ferritin, soluble transferrin receptors (sTfR), C-reactive protein (CRP), zinc, iron, copper, magnesium, folate and vitamin B12. Ordinal logit or multiple regression models were constructed to assess the risk for anemia and the associations among nutritional variables. RESULTS: The overall prevalence of anemia was 20.6%, of which 14% were mild cases and 6.38% moderate. Anemia was associated with iron deficiency (ID) in 42.17% of the cases, whereas ID coexisted with either folate or vitamin B12 deficiency in 9%. Only 2% of cases of anemia were associated with either folate or vitamin B12 deficiencies. CRP (coef: 0.17 g/dl) and third tertile of s-copper (coef: -0.85 g/dl) were associated to unexplained anemia (p<0.05). CONCLUSIONS: ID is the main cause of anemia in children <5 y. Folate and vitamin B12 concentrations were associated with anemia. CRP was associated to unexplained anemia. However, vitamin A deficiency, which is associated with anemia, was not studied. OBJETIVO: Describir las causas y severidad de la anemia y los factores nutricionales asociados con hemoglobina en niños anémicos <5 años. MATERIAL Y MÉTODOS: Estudiamos los niveles de hemoglobina y las concentraciones séricas de ferritina, receptores solubles de transferrina, proteína C reactiva (CRP), zinc, hierro, cobre, magnesio, vitamina B12 y folato en 981 niños. Se utilizaron modelos de regresión ordinal y regresiones lineales múltiples para evaluar el riesgo de severidad de anemia y la variabilidad en hemoglobina. RESULTADOS: La prevalencia de anemia fue de 20.6%; el 14 y 6.38% tenían anemia leve y moderada. La anemia se asoció con deficiencia de hierro (DH) en 42.17%; la DH coexistió con deficiencia de folatos y vitamina B12 en 9%. Sólo 2% de la anemia se asoció con deficiencia de folatos o vitamina B12. CRP (coef: 0.17 g/dl) y el tercer tercil de cobre (coef: -0.85 g/dl) se asociaron con anemia sin explicar (p<0.05). CONCLUSIONES: DH es la principal causa de anemia en niños <5 años. Las concentraciones de folato y vitamina B12 se asociaron con anemia. La CRP se asoció con anemia sin explicar. Sin embargo, la deficiencia de vitamina A, que se asocia con anemia, no fue estudiada.